Notices of Three Churches in North Uist, Benbecula, and Grimsay, said to have been built in the Fourteenth Century. (With Plans and Drawings.) (Proceedings of the Society of Antiquaries of Scotland, 1873)
[The journal notes that this paper will be published in the Archaeologia Scotica.]